Spontaneous Diaphragmatic Rupture in Hypermobile Type Ehlers-Danlos Syndrome - Ruchi Amin; Brett H. Waibel (Case Reports in Surgery)
Ehlers-Danlos Syndrome refers to a spectrum of connective tissue disorders that have a variety of clinical manifestations. In this case, we present a spontaneous diaphragmatic rupture in a patient with type III Ehlers-Danlos Syndrome. The patient presented with worsening shortness of breath after failure of medical therapy for a presumed pneumonia. A CT scan was obtained which showed diaphragmatic rupture with splenic herniation which was repaired in the operating room via thoracotomy. It is important to include diaphragmatic rupture in the differential diagnosis for patients with connective tissue disease and acute onset tachypnea and pain, as this complication has the potential for significant morbidity without prompt surgical intervention.